2015
DOI: 10.5209/rev_psic.2015.v12.n1.48905
|View full text |Cite
|
Sign up to set email alerts
|

Variables que predicen la aparición de sobrecarga en cuidadores primarios infor¬males de niños con cáncer

Abstract: ResumenEl propósito del estudio fue identificar las variables psicológicas y las características del cuidado que predicen la aparición de carga en cuidadores primarios informales (CPI) de niños con cáncer, en un hospital de la ciudad de México. La muestra no probabilística constó de 100 participantes, quienes contestaron una batería integrada por la encuesta de salud para el CPI, la escala de carga del cuidador de Zarit, los inventarios de ansiedad y depresión de Beck, la escala de apoyo familiar para CPI y la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
18

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 38 publications
(65 reference statements)
1
11
0
18
Order By: Relevance
“…The present study clearly unveiled that the mother in the role of caregiver of the child with cancer in the hospitalization process is permanently subjected to multiple overload factors. As in other studies, this study showed evidence that overload is a multidimensional experience (6,8,25) .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The present study clearly unveiled that the mother in the role of caregiver of the child with cancer in the hospitalization process is permanently subjected to multiple overload factors. As in other studies, this study showed evidence that overload is a multidimensional experience (6,8,25) .…”
Section: Discussionsupporting
confidence: 87%
“…It is usual for the mothers to undertake the main caregiver role and to get emotionally involved with the situation, while the fathers (paternal figure) act as providers and tend to emotionally distance themselves. This condition is easily perceived, especially in Latin countries where the mother plays several roles and is expected to develop competence in caring for the sick child (4)(5)(6) . Given these circumstances, it is necessary to value and foster the father's participation in caring for the sick child as a measure towards sharing this care with the mother; a desire expressed by some mothers in this study (26) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Mexico, to date, no studies have validated the RESI-M or some other scale used to measure resilience [ 33 , 34 ] in the caregiver population. This is despite the fact that the activities they carry out make them a vulnerable population [ 35 ], prone to presenting symptoms of stress, anxiety and depression [ 36 38 ] as well as experiencing a decrease in their quality of life [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%